PERAN MATEMATIKA DALAM PENENTUAN HAK WARIS ANAK ANGKAT: SOLUSI DIGITAL MELALUI APLIKASI I-WARIS - Sari, Niswa Istiqlalia; Muhasshanah, Muhasshanah; Mawardi, Mawardi (LP2M Universitas Ibrahimy, 2025)
In Islamic law, the distribution of inheritance must be determined fairly based on the Faraidh principle, which regulates the share of each heir according to Islamic Sharia. However, in practice, manual calculations in inheritance distribution often lead to conflicts and errors, especially in more complex cases such as the distribution of inheritance for adopted children. This study aims to analyze the role of Faraidh mathematics in determining the inheritance of adopted children and evaluate the effectiveness of the use of the I-waris application. The research method used is a qualitative descriptive approach with a literature study of Sharia sources and an analysis of the effectiveness of the I-waris application. Data were obtained from document reviews and application feature trials. The results of the study indicate that the integration of mathematics through digital applications such as I-Waris is an innovative solution in dealing with the complexity of determining inheritance rights, especially when involving adopted children. Based on the research that has been conducted, it can be concluded that the application of faraidh mathematics through the I-waris application has proven effective in solving the problem of calculating the inheritance of adopted children.